2023
DOI: 10.3389/fpsyg.2023.1089362
|View full text |Cite
|
Sign up to set email alerts
|

The impact of continuous use intention of cooperative members on new agricultural technologies

Abstract: The widespread application of new agricultural technologies promotes an increase in agricultural production and income and in the optimization and adjustment of the industrial structure. However, there are problems such as low promotion efficiency, an insufficient transformation of achievements, and a mismatch of supply and demand in the process of promotion. Based on the research context of farmer cooperatives in China, this study explores the factors influencing the continuous use intention of cooperative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This also happens to agricultural cooperatives. In reality, many agricultural cooperatives still have difficulty contextualizing technology when diagnosing new challenges (Anh, 2022;Jia et al, 2023;Liu et al, 2022;Luo et al, 2017;Moral and Uclés, 2022). This situation creates a dilemma.…”
Section: Existing Situationmentioning
confidence: 99%
“…This also happens to agricultural cooperatives. In reality, many agricultural cooperatives still have difficulty contextualizing technology when diagnosing new challenges (Anh, 2022;Jia et al, 2023;Liu et al, 2022;Luo et al, 2017;Moral and Uclés, 2022). This situation creates a dilemma.…”
Section: Existing Situationmentioning
confidence: 99%
“…On the other hand, past studies have revealed that agricultural cooperatives that do not prioritize technology further reduce their success rate. This happens to the majority of rural farmers in China, especially in Sichuan Province (Ma & Abdulai, 2017;Jia et al, 2023;Liu et al, 2022). In other words, the failure or success of agricultural cooperatives is also determined by the technology used.…”
mentioning
confidence: 99%